Supported noble metal catalyst with high-density surface hydroxyl groups as well as preparation method and application of supported noble metal catalyst

By preparing a supported precious metal catalyst with high-density surface hydroxyl groups, the multi-site synergistic catalytic active sites of titanium dioxide support and precious metal nanoparticles are used to solve the problem of insufficient activity of existing catalysts at room temperature, and efficient and stable formaldehyde oxidation and decomposition is achieved.

CN119633806APending Publication Date: 2025-03-18SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411503604.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing supported precious metal catalysts have insufficient activity in catalyzing formaldehyde oxidation at room temperature, which is difficult to meet practical needs.

Method used

By preparing a supported noble metal catalyst with high-density surface hydroxyl groups, the titanium dioxide support exposed to the {100} crystal plane and the multi-site synergistic catalytic active sites of the noble metal nanoparticles can be achieved efficient oxidation and decomposition of formaldehyde.

Benefits of technology

The catalyst exhibits excellent formaldehyde oxidation activity and stability at room temperature, and its comprehensive catalytic performance is better than the currently reported supported precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633806A_ABST
    Figure CN119633806A_ABST
Patent Text Reader

Abstract

The invention discloses a supported noble metal catalyst with high-density surface hydroxyl groups as well as a preparation method and application of the supported noble metal catalyst. The preparation method comprises the following steps: by taking titanium hydroxide and ammonium sulfate as starting materials, preparing a titanium dioxide carrier with an exposed {100} crystal face through a hydrothermal method; the preparation method comprises the following steps: dispersing a titanium dioxide carrier with exposed {100} crystal faces, noble metal salt and / or noble metal acid and alkali metal hydroxide in water to obtain a mixed solution, and carrying out stirring dipping, solvent evaporation drying, drying and reduction heat treatment to obtain the supported noble metal catalyst with high-density surface hydroxyl groups. According to the preparation method, raw materials are easy to obtain, operation is easy and convenient, mass production is facilitated, the prepared catalyst has high intrinsic performance and rich surface hydroxyl groups, and the comprehensive catalytic performance of the catalyst is superior to that of most reported noble metal catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and specifically relates to a supported noble metal catalyst with high-density surface hydroxyl groups, and a preparation method and application thereof. Background Art

[0002] Formaldehyde is one of the most common and toxic indoor air pollutants. Exposure to an environment with excessive formaldehyde can cause a variety of serious diseases, such as asthma, nasopharyngeal cancer, leukemia, etc., posing a huge threat to human health. Therefore, the development of safe and efficient formaldehyde removal technology is crucial to improving the air quality of residential environments and reducing health risks. Among the existing formaldehyde removal technologies, catalytic oxidation has become the preferred option due to its advantages of high removal efficiency, non-toxic products, and energy saving. The core of the development of catalytic oxidation formaldehyde removal lies in the development of efficient and low-cost formaldehyde oxidation catalysts to achieve the oxidation and degradation of formaldehyde into CO2 and H2O at room temperature.

[0003] After more than 20 years of research and development, formaldehyde oxidation catalysts have formed two major branches: supported precious metals (Pt, Au, Pd and Ag, etc.) and non-precious metal oxides (MnO2, CeO2 and Co3O4, etc.). Although non-precious metal oxides are cheap, their activity is generally low, and they usually require a temperature above 60°C to catalyze the complete oxidation of formaldehyde. In contrast, most precious metal catalysts have excellent low-temperature catalytic activity, and some supported precious metal catalysts can catalyze the complete oxidation of formaldehyde at room temperature, but their commercial application is restricted by high material costs. In view of the huge difference in activity between the two, supported precious metal catalysts are still the most promising formaldehyde oxidation catalysts. In recent years, the development of efficient and inexpensive supported precious metal catalysts has become the mainstream trend in the development of formaldehyde catalytic oxidation technology. According to literature reports, the formaldehyde oxidation catalytic activity of supported precious metal catalysts can be effectively improved by optimizing the dispersion state of precious metal particles and regulating the composition and structure of the carrier. But in general, the catalytic activity of precious metal catalysts is far from meeting practical needs (as reflected in the low catalytic reaction rate per unit mass of precious metal) [Appl.Surf.Sci.475(2019)237–255]. Therefore, the development of advanced design concepts and controllable synthesis methods for supported precious metal catalysts remains a key issue to be solved in the process of promoting the practical application of formaldehyde catalytic oxidation technology. Summary of the invention

[0004] In view of the shortcomings and deficiencies of the above prior art, the object of the present invention is to provide a supported noble metal catalyst with a high density of surface hydroxyl groups and a preparation method and application thereof.

[0005] The supported precious metal catalyst provided by the present invention has the characteristics of highly dispersed precious metal nanoparticles and the interface area between the precious metal particles and the carrier oxide is rich in hydroxyl groups and oxygen vacancies, providing high-density multi-site synergistic catalytic active sites, which can efficiently and stably catalyze the oxidative decomposition of formaldehyde at room temperature, and exhibit excellent comprehensive catalytic performance.

[0006] The preparation method provided by the invention has readily available raw materials, is simple to operate and is convenient for mass production.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a supported noble metal catalyst having a high density of surface hydroxyl groups comprises the following steps:

[0009] A titanium dioxide carrier with exposed {100} crystal faces, a noble metal salt and / or a noble metal acid, and an alkali metal hydroxide are dispersed in water to obtain a mixed solution, and a supported noble metal catalyst with a high density of surface hydroxyl groups is obtained through stirring and impregnation, solvent evaporation, drying, and reduction heat treatment.

[0010] Preferably, the titanium dioxide carrier with exposed {100} crystal plane is prepared by a hydrothermal method using titanium hydroxide and ammonium sulfate;

[0011] Preferably, the titanium dioxide carrier with exposed {100} crystal planes has a morphology of nanorods; the length of the nanorods is 10-100 nm and the width is 1-10 nm.

[0012] Preferably, the method for preparing the titanium dioxide support with exposed {100} crystal plane comprises the following steps:

[0013] Titanium hydroxide and ammonium sulfate are dissolved in a mixed solvent of water and isopropanol, and then subjected to hydrothermal reaction after ultrasonic dispersion. After cooling, the solid product is washed and dried to obtain a titanium dioxide carrier with exposed {100} crystal planes.

[0014] Further preferably, in the method for preparing the titanium dioxide support exposing the {100} crystal plane,

[0015] The molar ratio of titanium hydroxide to ammonium sulfate is 17:(2-6);

[0016] The volume ratio of water to isopropanol in the mixed solvent is 1:(1-3);

[0017] The molar volume ratio of the titanium hydroxide and the mixed solvent is (10-30) mmol: 30 mL;

[0018] The ultrasonic dispersion time is 5-60min;

[0019] The temperature of the hydrothermal reaction is 130-180°C, and the time of the hydrothermal reaction is 12-36h;

[0020] The cooling is natural cooling to room temperature;

[0021] The washing is centrifugal washing; the drying temperature is 60-150° C. and the drying time is 3-24 hours.

[0022] Preferably, the noble metal salt is at least one of tetraammineplatinum nitrate [Pt(NH3)4](NO3)2, sodium hexahydroxyplatinate (IV) Na2[Pt(OH)6], potassium hexahydroxyplatinate (IV) K2[Pt(OH)6], sodium chloroplatinate Na2PtCl6, platinum nitrate Pt(NO3)2, palladium nitrate Pd(NO3)2, iridium chloride IrCl3, platinum hydroxide Pt(OH)4, and gold hydroxide Au(OH)3; the noble metal acid refers to at least one of hexahydroxyplatinic acid (IV) H2[Pt(OH)6], chloroplatinic acid H2PtCl6, chloroauric acid H2AuCl4, and iridic acid H2IrCl6;

[0023] Preferably, the alkali metal hydroxide includes at least one of LiOH, NaOH, KOH, RbOH, and CsOH;

[0024] Preferably, the total concentration of the noble metal in the mixed solution is 0.1-50 mM; the concentration of the alkali metal hydroxide in the mixed solution is 0.1-50 mM; the mass ratio of the total mass of the noble metal in the noble metal salt and / or noble metal acid to the mass ratio of the titanium dioxide support with exposed {100} crystal face is 0.1-5 wt%; the mass ratio of the total mass of the alkali metal in the mixed solution to the mass ratio of the titanium dioxide support with exposed {100} crystal face is 0.1-50 wt%;

[0025] Preferably, the stirring and dipping time is 0.1-5h;

[0026] Preferably, the temperature for evaporating the solvent to dryness is 50-80°C;

[0027] Preferably, the cooling is natural cooling to room temperature;

[0028] Preferably, the drying temperature is 60-150° C. and the drying time is 3-24 hours.

[0029] Preferably, the atmosphere of the reduction heat treatment is a hydrogen-containing atmosphere; the hydrogen-containing atmosphere is a hydrogen / argon mixed gas containing 1%-100% hydrogen by volume; the temperature of the reduction heat treatment is 100-400°C, and the time of the reduction heat treatment is 0.5-5h.

[0030] The preparation method mentioned above prepares a supported noble metal catalyst having a high density of surface hydroxyl groups.

[0031] Preferably, the supported noble metal catalyst is composed of a noble metal and a titanium dioxide carrier with exposed {100} crystal faces; the noble metal is dispersed in the form of fine nanoparticles on the surface of the titanium dioxide carrier with exposed {100} crystal faces.

[0032] Further preferably, the noble metal is at least one of Pt, Pd, Au, and Ir;

[0033] Further preferably, the particle size of the noble metal is 0.5-5 nm;

[0034] Further preferably, the surface of the titanium dioxide support with exposed {100} crystal plane is rich in hydroxyl groups and oxygen vacancy structures;

[0035] More preferably, the noble metal, hydroxyl and oxygen vacancies constitute multi-site active sites. Multi-site active sites refer to the vicinity of the noble metal nanoparticles and the hydroxyl and oxygen vacancies in the carrier.

[0036] Application of the above-mentioned supported noble metal catalyst with high density of surface hydroxyl groups in catalytic oxidation of formaldehyde.

[0037] Design principle of the present invention:

[0038] Earlier, the applicant used in situ infrared characterization technology to study the oxidation mechanism of formaldehyde on defective oxide-supported platinum catalysts and found that the oxidation of formaldehyde on the catalyst surface is a multi-molecular, multi-element step reaction involving formaldehyde, oxygen and water molecules [ACS Catal. 12 (2022) 5565–5573; J. Hazard. Mater. 416 (2021) 126224]. For this reaction, designing and synthesizing active sites with multiple different functions to improve the adsorption and activation of each reactant / intermediate product is the key to developing high-performance catalysts. The oxidation process of formaldehyde usually starts with the formation of dimethoxyl group (DOM, chemical formula H2CO2), which is then converted into formate (HCOO) intermediate product and follows the following two possible reaction pathways: (I) HCOO→CO→CO2+H2O; (II) HCOO+OH→CO2+H2O. During the reaction, the hydroxyl groups on the catalyst surface can not only act as adsorption sites for formaldehyde molecules, but also effectively promote the conversion of dimethoxyl group to formate and the direct oxidation of formate to the final product of carbon dioxide. Based on this mechanism, the present invention provides a supported precious metal catalyst with a high density of surface hydroxyl groups, and provides a simple and easy preparation method to achieve it. First, a hydrothermal method is used to prepare titanium dioxide with exposed {100} crystal faces as a carrier; then, an impregnation method is used to adsorb precious metal precursors (precious metal salts, precious metal acids, etc.) and alkali metal hydroxides on the surface of the carrier to obtain an impregnated sample; finally, the impregnated sample is placed in a hydrogen-containing atmosphere for heat treatment to obtain metallic precious metal nanoparticles and create oxygen vacancies on the titanium dioxide surface. The created oxygen vacancies can be used as water molecule adsorption sites, thereby activating water to produce a large number of surface hydroxyl groups as formaldehyde molecule adsorption sites and directly participate in the formaldehyde oxidation reaction. In summary, the formaldehyde oxidation catalyst provided by the present invention has both high intrinsic activity and abundant active sites.

[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] (1) The titanium dioxide carrier with exposed {100} crystal faces of the present invention has a strong ability to adsorb water and can generate a large number of surface hydroxyl groups to provide active sites for the adsorption and activation of reactants; its preparation method is simple and controllable, and is convenient for mass production.

[0041] (2) The supported noble metal catalyst material of the present invention effectively optimizes both intrinsic activity and the number of active sites. Titanium dioxide with exposed {100} crystal faces having strong water adsorption capacity is selected as the carrier, and on this basis, fine and dispersed noble metal particles are introduced by co-impregnation of alkali metal hydroxide and noble metal precursor, which together constitute multiple synergistic active sites of noble metal, hydroxyl and oxygen vacancies.

[0042] (3) The preparation method of the supported noble metal catalyst of the present invention has readily available raw materials, simple process, and is convenient for mass production.

[0043] (4) The multi-site supported precious metal catalyst provided by the present invention has excellent room temperature catalytic formaldehyde oxidation activity due to the high density of surface hydroxyl groups, and also has good stability and moisture resistance. The comprehensive catalytic performance is better than the currently reported supported precious metal catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the X-ray diffraction pattern of the 0.5 wt % Pt and 5 wt % KOH co-loaded on the TiO2{100} catalyst (denoted as: Pt / TiO2{100}-K) obtained in Example 2 of the present invention.

[0045] Figure 2 This is a transmission electron micrograph of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention.

[0046] Figure 3 This is a high-angle annular dark field-scanning transmission electron micrograph of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention.

[0047] Figure 4 This is the X-ray photoelectron spectrum of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention in the O1s region.

[0048] Figure 5 This is a diagram showing the formaldehyde catalytic oxidation performance of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention.

[0049] Figure 6 This is a graph showing the stability test results of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention.

[0050] Figure 7 This is a graph showing the moisture resistance test results of the Pt / TiO2{100}-K catalyst obtained in Example 2 of the present invention.

[0051] Figure 8 This is the X-ray diffraction pattern of the 0.5 wt % Pd and 5 wt % KOH co-loaded on the TiO2{100} catalyst (denoted as: Pd / TiO2{100}-K) obtained in Example 3 of the present invention.

[0052] Fig. 9 This is a high-angle annular dark field-scanning transmission electron micrograph of the Pd / TiO2{100}-K catalyst obtained in Example 3 of the present invention.

[0053] Fig.10This is the X-ray photoelectron spectrum of the Pd / TiO2{100}-K catalyst obtained in Example 3 of the present invention in the O1s region.

[0054] Fig.11 This is a diagram showing the formaldehyde catalytic oxidation performance of the Pd / TiO2{100}-K catalyst obtained in Example 3 of the present invention.

[0055] Fig.12 This is a graph showing the stability test results of the Pd / TiO2{100}-K catalyst obtained in Example 3 of the present invention.

[0056] Fig.13 This is a graph showing the moisture resistance test results of the Pd / TiO2{100}-K catalyst obtained in Example 3 of the present invention.

[0057] Fig.14 This is the X-ray diffraction pattern of the 0.5 wt % Pt loaded on TiO2{100} catalyst (denoted as: Pt / TiO2{100}) obtained in Comparative Example 1 of the present invention.

[0058] Fig.15 This is a high-angle annular dark field-scanning transmission electron micrograph of the Pt / TiO2{100} catalyst obtained in Comparative Example 1 of the present invention.

[0059] Fig.16 This is the X-ray photoelectron spectrum of the Pt / TiO2{100} catalyst obtained in Comparative Example 1 of the present invention in the O1s region.

[0060] Fig.17 This is a formaldehyde catalytic oxidation performance diagram of the Pt / TiO2{100} catalyst obtained in Comparative Example 1 of the present invention.

[0061] Fig.18 This is a formaldehyde catalytic oxidation performance diagram of the Pt / TiO2{101} catalyst obtained in Comparative Example 2 of the present invention.

[0062] Fig.19 This is a transmission electron micrograph of the Pt / TiO2{101}-K catalyst obtained in Comparative Example 3 of the present invention.

[0063] Fig. 20 This is a diagram showing the formaldehyde catalytic oxidation performance of the Pt / TiO2{101}-K catalyst obtained in Comparative Example 3 of the present invention.

[0064] Fig.21 This is a diagram showing the formaldehyde catalytic oxidation performance of the Pt / TiO2{001} catalyst obtained in Comparative Example 4 of the present invention.

[0065] Fig. 22 This is a transmission electron micrograph of the Pt / TiO2{001}-K catalyst obtained in Comparative Example 4 of the present invention.

[0066] Fig.23 This is a formaldehyde catalytic oxidation performance diagram of the Pt / TiO2{001}-K catalyst obtained in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0067] The present invention is further described in detail below in conjunction with embodiments and drawings, but the implementation manner and protection scope of the present invention are not limited thereto.

[0068] Example 1

[0069] Preparation of titanium dioxide support with exposed {100} crystal face:

[0070] 17 mmol titanium hydroxide and 3.8 mmol ammonium sulfate were added to a mixed solvent of 15 mL water and 15 mL isopropanol and ultrasonicated for 30 minutes. The suspension was then transferred to a 50 mL polytetrafluoroethylene reactor. After constant temperature reaction at 180°C for 24 hours, it was naturally cooled to room temperature. The solid product was centrifugally washed (with ultrapure water and anhydrous ethanol, respectively) and dried (150°C, 6 hours) to obtain a titanium dioxide carrier with exposed {100} crystal planes.

[0071] Example 2

[0072] (1) Catalyst preparation:

[0073] Synthesis of Pt / TiO2{100}-K catalyst: 100 mg of the TiO2{100} carrier prepared in Example 1, 39 μL of [Pt(NH3)4](NO3)2 (64.6 mM) and 1 mL of KOH (64.6 mM) were dispersed in 10 mL of deionized water and stirred for 1 h. The solid sample was collected by rotary evaporation (60 ° C) and vacuum dried at 80 ° C for 6 h to obtain an impregnated sample. The impregnated sample was heated to 300 ° C in a H2 atmosphere at a heating rate of 5 ° C min -1 After being treated at a constant temperature for 1 hour, the mixture was naturally cooled to room temperature to obtain the target catalyst.

[0074] (2) Catalyst structure / oxygen element chemical state characterization:

[0075] The X-ray diffraction pattern of the Pt / TiO2{100}-K catalyst obtained in this example shows ( Figure 1 ), the obtained catalyst is composed of rutile TiO2.

[0076] Transmission electron micrographs show ( Figure 2 ), TiO2{100} is a nanorod morphology, and the interplanar spacing corresponding to the (100) crystal plane is measured to be 0.19nm.

[0077] High-angle annular dark field-scanning transmission electron micrographs show ( Figure 3 ), a large number of fine and dispersed Pt nanoparticles with a size of 0.8 to 2.0 nm are evenly distributed on its surface.

[0078] X-ray photoelectron spectroscopy shows ( Figure 4 ), a signal attributed to surface oxygen appeared in the O 1s orbital spectrum, and the peak area ratio attributed to surface oxygen and lattice oxygen signals reached 14.3%, proving that there are a large number of hydroxyl groups on the surface of Pt / TiO2{100}-K catalyst.

[0079] (3) Catalytic performance test of the catalyst Pt / TiO2{100}-K obtained in this example:

[0080] Changes in catalytic activity of Pt / TiO2{100}-K catalyst at different temperatures ( Figure 5 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), 80 ppm formaldehyde can be completely degraded into CO2 and H2O at a reaction temperature of 20°C, indicating that it has excellent low-temperature catalytic activity; in addition, at room temperature (25°C), the mass specific reaction rate of the catalyst is as high as 105.7 μmol g Pt -1 s -1 , this catalytic activity is at the top level among the reported formaldehyde oxidation catalysts. Test conditions: different temperatures, gas composition is a mixture of 80ppm formaldehyde and synthetic air, relative humidity is 50%, gas space velocity is 500Lg cat -1 h -1 .

[0081] Figure 6 The stability test results of the Pt / TiO2{100}-K catalyst are given. After 24h isothermal measurement, the catalyst activity did not show obvious attenuation, indicating that the catalyst has good stability. Test conditions: The gas composition is a mixture of 80ppm formaldehyde and synthetic air, the relative humidity is 50%, and the gas space velocity is 750L g cat -1 h -1 , the temperature is 25℃.

[0082] Figure 7 The results of the moisture resistance test of the Pt / TiO2{100}-K catalyst are given. Under different humidity conditions, the catalyst activity shows slight fluctuations, indicating that the catalyst has good moisture resistance. Test conditions: different humidity, gas composition is a mixture of 80ppm formaldehyde and synthetic air, gas space velocity is 750L g cat -1 h -1, the temperature is 25℃.

[0083] Example 3

[0084] (1) Catalyst preparation:

[0085] In the synthesis method of this embodiment, only [Pt(NH3)4](NO3)2 is replaced with palladium nitrate Pd(NO3)2, and the loading amount of precious metal Pd is kept at 0.5wt%. The other preparation conditions are consistent with Example 2.

[0086] (2) Catalyst structure / oxygen element chemical state characterization:

[0087] The X-ray diffraction pattern of the Pd / TiO2{100}-K catalyst obtained in this example shows ( Figure 8 ), the obtained catalyst is composed of rutile TiO2.

[0088] High-angle annular dark field-scanning transmission electron micrographs show ( Fig. 9 ), TiO2{100} is in the shape of nanorods, and a large number of fine dispersed Pd nanoparticles with a size of 0.8 to 2.0 nm are evenly distributed on its surface.

[0089] X-ray photoelectron spectroscopy shows ( Fig.10 ), a signal attributed to surface oxygen appeared in the O 1s orbital spectrum, and the peak area ratio of the surface oxygen to lattice oxygen signals reached 13.8%, proving that a large number of hydroxyl groups existed on the surface of the Pd / TiO2{100} catalyst.

[0090] (3) Catalytic performance test of the catalyst Pd / TiO2{100}-K obtained in this example:

[0091] Changes in catalytic activity of Pd / TiO2{100}-K catalyst at different temperatures ( Fig.11 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), 80 ppm formaldehyde can be completely degraded into CO2 and H2O at a reaction temperature of 25°C, indicating that it has excellent low-temperature catalytic activity; in addition, at room temperature (25°C), the mass specific reaction rate of the catalyst is as high as 88.9 μmol g Pt -1 s -1 , this catalytic activity is at the top level among the reported formaldehyde oxidation catalysts. Test conditions: different temperatures, gas composition is a mixture of 80ppm formaldehyde and synthetic air, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0092] Fig.12 The stability test results of the Pd / TiO2{100}-K catalyst are given. After 24h isothermal measurement, the catalyst activity did not show obvious attenuation, indicating that the catalyst has good stability. Test conditions: The gas composition is a mixture of 80ppm formaldehyde and synthetic air, the relative humidity is 50%, and the gas space velocity is 750L g cat -1 h -1 , the temperature is 25℃.

[0093] Fig.13 The results of the moisture resistance test of the Pd / TiO2{100}-K catalyst are given. Under different humidity conditions, the catalyst activity shows slight fluctuations, indicating that the catalyst has good moisture resistance. Test conditions: different humidity, gas composition is a mixture of 80ppm formaldehyde and synthetic air, gas space velocity is 750L g cat -1 h -1 , the temperature is 25℃.

[0094] Comparative Example 1

[0095] (1) Catalyst preparation:

[0096] In the synthesis method of the catalyst of this comparative example, only alkali metal hydroxide (KOH) is not added, and the other preparation conditions are consistent with Example 2.

[0097] (2) Structural characterization of catalysts:

[0098] The X-ray diffraction pattern of the Pt / TiO2{100} catalyst obtained in this example shows ( Fig.14 ), the physical phase of the obtained catalyst is anatase TiO2.

[0099] High-angle annular dark field-scanning transmission electron micrographs show ( Fig.15 ), TiO2{100} is in the shape of nanorods, and a large number of fine and dispersed Pt nanoparticles with a size of 1.0 to 3.0 nm are evenly distributed on its surface.

[0100] X-ray photoelectron spectroscopy shows ( Fig.16 ), a signal attributed to surface oxygen appeared in the O 1s orbital spectrum, and the peak area ratio of the surface oxygen to lattice oxygen signals was only 7.8%, proving that there were fewer hydroxyl groups on the surface of the Pt / TiO2{100} catalyst.

[0101] (3) Catalytic activity test of the catalyst Pt / TiO2{100} obtained in this example:

[0102] Changes in catalytic activity of Pt / TiO2{100} catalyst at different temperatures ( Fig.17 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), the Pt / TiO2{100} catalyst completely degrades 80 ppm formaldehyde into CO2 and H2O at a reaction temperature of 40°C, which is much higher than the complete conversion temperature (20°C) of the catalyst in Example 2; in addition, at room temperature (25°C), the mass specific reaction rate of the catalyst is only 56.5 μmol g Pt -1 s -1 Activity test conditions: different temperatures, gas composition is 80ppm formaldehyde and synthetic air mixture, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0103] Comparative Example 2

[0104] (1) Preparation of titanium dioxide carrier with exposed {101} crystal plane: In the synthesis method of the titanium dioxide carrier with exposed {101} crystal plane in this comparative example, only ammonium sulfate was replaced with ammonium chloride, and the other preparation conditions were consistent with those in Example 1.

[0105] (2) Catalyst preparation: In the synthesis method of the catalyst of this comparative example, only the titanium dioxide support with exposed {100} crystal faces is replaced with a titanium dioxide support with exposed {101} crystal faces, and no alkali metal hydroxide (KOH) is added. The other preparation conditions are consistent with those of Example 2.

[0106] (3) Catalytic activity test of the catalyst Pt / TiO2{101} obtained in this comparative example:

[0107] Changes in catalytic activity of Pt / TiO2{101} catalyst at different temperatures ( Fig.18 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), the Pt / TiO2{101} catalyst completely degrades 80 ppm formaldehyde into CO2 and H2O at a reaction temperature of 40°C, which is much higher than the complete conversion temperature (20°C) of the catalyst in Example 2; in addition, at room temperature (25°C), the mass specific reaction rate of the catalyst is only 40.6 μmol g Pt -1 s -1 Activity test conditions: different temperatures, gas composition is 80ppm formaldehyde and synthetic air mixture, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0108] Comparative Example 3

[0109] In the synthesis method of the catalyst of this comparative example, only the titanium dioxide carrier exposing the {100} crystal plane is replaced with a titanium dioxide carrier exposing the {101} crystal plane, and the other preparation conditions are consistent with those of Example 2.

[0110] (1) Structural characterization of catalysts:

[0111] Transmission electron micrographs show ( Fig.19 ), TiO2{101} is a nanoparticle morphology, and the interplanar spacing corresponding to the (101) crystal plane is measured to be 0.38nm.

[0112] (2) Catalytic activity test of the catalyst Pt / TiO2{101}-K obtained in this comparative example:

[0113] Changes in catalytic activity of Pt / TiO2{101}-K catalyst at different temperatures ( Fig. 20 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), the reaction temperature of Pt / TiO2{101}-K catalyst to completely degrade 80 ppm formaldehyde into CO2 and H2O requires 25°C, which is much higher than the complete conversion temperature (20°C) of the catalyst in Example 1; in addition, under room temperature (25°C) reaction conditions, the mass specific reaction rate of the catalyst is only 80.9 μmol g Pt -1 s -1 Activity test conditions: different temperatures, gas composition is 80ppm formaldehyde and synthetic air mixture, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0114] Comparative Example 4

[0115] (1) Preparation of titanium dioxide support with exposed {001} crystal plane:

[0116] 72 mmol of hydrofluoric acid (1.44 mL, 40%) was slowly dripped into 35.2 mmol of isopropyl titanate (10 mL, 97%), and then the suspension was transferred to a 50 mL polytetrafluoroethylene reactor. After constant temperature reaction at 180°C for 24 hours, it was naturally cooled to room temperature. The solid product was centrifugally washed (with ultrapure water and anhydrous ethanol, respectively) and dried (150°C, 6 hours) to obtain a titanium dioxide carrier with exposed {001} crystal plane.

[0117] (2) Catalyst preparation: In the synthesis method of the catalyst of this comparative example, only the titanium dioxide support with exposed {100} crystal face is replaced with a titanium dioxide support with exposed {001} crystal face, and no alkali metal hydroxide (KOH) is added. The other preparation conditions are consistent with those of Example 2.

[0118] (3) Catalytic activity test of the catalyst Pt / TiO2{001} obtained in this comparative example:

[0119] Changes in catalytic activity of Pt / TiO2{001} catalyst at different temperatures ( Fig.21 ) shows that under high airspeed conditions (500L g cat -1 h -1 ), the reaction temperature of the Pt / TiO2{001} catalyst to completely degrade 80 ppm formaldehyde into CO2 and H2O is 40°C, which is much higher than the complete conversion temperature (20°C) of the catalyst in Example 2; in addition, under room temperature (25°C) reaction conditions, the mass specific reaction rate of the catalyst is only 23.9 μmol g Pt -1 s -1 Activity test conditions: different temperatures, gas composition is 80ppm formaldehyde and synthetic air mixture, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0120] Comparative Example 5

[0121] In the synthesis method of the catalyst of this comparative example, only the titanium dioxide carrier exposing the {100} crystal plane is replaced with a titanium dioxide carrier exposing the {001} crystal plane, and the other preparation conditions are consistent with those of Example 2.

[0122] (1) Structural characterization of catalysts:

[0123] Transmission electron micrographs show ( Fig. 22 ), TiO2{001} is a nanosheet morphology, and the interplanar spacing corresponding to the (001) crystal plane is measured to be 0.24nm.

[0124] (2) Catalytic activity test of the catalyst Pt / TiO2{001}-K obtained in this comparative example:

[0125] Changes in catalytic activity of Pt / TiO2{001}-K catalyst at different temperatures ( Fig.23 ) shows that under high airspeed conditions (500L g cat -1 h -1), the reaction temperature of Pt / TiO2{001}-K catalyst to completely degrade 80 ppm formaldehyde into CO2 and H2O requires 35°C, which is much higher than the complete conversion temperature (20°C) of the catalyst in Example 2; in addition, under room temperature (25°C) reaction conditions, the mass specific reaction rate of the catalyst is only 56.9 μmol g Pt -1 s -1 Activity test conditions: different temperatures, gas composition is 80ppm formaldehyde and synthetic air mixture, relative humidity is 50%, gas space velocity is 500L g cat -1 h -1 .

[0126] The above embodiments are partial implementation methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a supported noble metal catalyst having a high density of surface hydroxyl groups, characterized in that: The following steps are involved: A titanium dioxide carrier with exposed {100} crystal faces, a noble metal salt and / or a noble metal acid, and an alkali metal hydroxide are dispersed in water to obtain a mixed solution, and a supported noble metal catalyst with a high density of surface hydroxyl groups is obtained through stirring and impregnation, solvent evaporation, drying, and reduction heat treatment.

2. The preparation method according to claim 1, characterized in that: The titanium dioxide carrier with exposed {100} crystal plane is prepared by a hydrothermal method using titanium hydroxide and ammonium sulfate; The titanium dioxide carrier with exposed {100} crystal plane has a nanorod shape; the nanorod has a length of 10-100 nm and a width of 1-10 nm.

3. The preparation method according to claim 2, characterized in that: The method for preparing the titanium dioxide carrier with exposed {100} crystal plane comprises the following steps: Titanium hydroxide and ammonium sulfate are dissolved in a mixed solvent of water and isopropanol, and then subjected to hydrothermal reaction after ultrasonic dispersion. After cooling, the solid product is washed and dried to obtain a titanium dioxide carrier with exposed {100} crystal planes.

4. The preparation method according to claim 3, characterized in that: In the method for preparing the titanium dioxide support with exposed {100} crystal planes, The molar ratio of titanium hydroxide to ammonium sulfate is 17:(2-6); The volume ratio of water to isopropanol in the mixed solvent is 1:(1-3); The molar volume ratio of the titanium hydroxide and the mixed solvent is (10-30) mmol: 30 mL; The ultrasonic dispersion time is 5-60min; The temperature of the hydrothermal reaction is 130-180°C, and the time of the hydrothermal reaction is 12-36h; The cooling is natural cooling to room temperature; The washing is centrifugal washing; the drying temperature is 60-150° C. and the drying time is 3-24 hours.

5. The preparation method according to claim 1, characterized in that: The noble metal salt is at least one of tetraammineplatinum nitrate [Pt(NH3)4](NO3)2, sodium hexahydroxyplatinate (IV) Na2[Pt(OH)6], potassium hexahydroxyplatinate (IV) K2[Pt(OH)6], sodium chloroplatinate Na2PtCl6, platinum nitrate Pt(NO3)2, palladium nitrate Pd(NO3)2, iridium chloride IrCl3, platinum hydroxide Pt(OH)4, and gold hydroxide Au(OH)3; the noble metal acid is at least one of hexahydroxyplatinic acid (IV) H2[Pt(OH)6], chloroplatinic acid H2PtCl6, chloroauric acid H2AuCl4, and iridic acid H2IrCl6; The alkali metal hydroxide includes at least one of LiOH, NaOH, KOH, RbOH, and CsOH; The total concentration of the noble metal in the mixed solution is 0.1-50 mM; the concentration of the alkali metal hydroxide in the mixed solution is 0.1-50 mM; the mass ratio of the total mass of the noble metal in the noble metal salt and / or noble metal acid to the mass ratio of the titanium dioxide carrier exposing the {100} crystal face is 0.1-5 wt%; the mass ratio of the total mass of the alkali metal in the mixed solution to the mass ratio of the titanium dioxide carrier exposing the {100} crystal face is 0.1-50 wt%; The stirring and dipping time is 0.1-5h; The temperature of evaporating the solvent to dryness is 50-80°C; The cooling is natural cooling to room temperature; The drying temperature is 60-150° C. and the drying time is 3-24 hours.

6. The preparation method according to claim 1, characterized in that: The atmosphere of the reduction heat treatment is a hydrogen-containing atmosphere; the hydrogen-containing atmosphere is a hydrogen / argon mixed gas containing 1%-100% hydrogen by volume; the temperature of the reduction heat treatment is 100-400°C, and the time of the reduction heat treatment is 0.5-5h.

7. A supported noble metal catalyst having a high density of surface hydroxyl groups prepared by the preparation method according to any one of claims 1 to 6.

8. The supported noble metal catalyst having a high density of surface hydroxyl groups according to claim 7, characterized in that: The supported noble metal catalyst consists of noble metal and a titanium dioxide carrier with exposed {100} crystal plane; the noble metal is dispersed on the surface of the titanium dioxide carrier with exposed {100} crystal plane in the form of fine nanoparticles.

9. The supported noble metal catalyst having a high density of surface hydroxyl groups according to claim 8, characterized in that: The noble metal is at least one of Pt, Pd, Au, and Ir; The particle size of the noble metal is 0.5-5 nm; The surface of the titanium dioxide carrier with exposed {100} crystal plane is rich in hydroxyl groups and oxygen vacancy structure; the noble metal, hydroxyl groups and oxygen vacancies constitute multi-site active sites.

10. Use of the supported noble metal catalyst having a high density of surface hydroxyl groups according to any one of claims 7 to 9 in catalytic oxidation of formaldehyde.

Citation Information

Patent Citations

  • Formaldehyde degrading catalyst and preparation method thereof

    CN106824256A

  • Supported noble metal formaldehyde removal catalyst with high-density concerted catalytic active sites as well as preparation method and application of supported noble metal formaldehyde removal catalyst

    CN116078376A